Financial Distress and Abnormal Operating Cash Flows: Firm-Size Moderation of Auditor Going-Concern Opinions - Muhammad Jufrianci Dewa; Lilis Ardini; Suwardi Bambang H (E-Jurnal Akuntansi, 2025)
Auditors routinely assess financial distress and unusual patterns in operating cash flows when judging a client’s ability to continue as a going concern. This study investigates whether (i) financial distress and (ii) abnormal operating cash flows influence the likelihood of receiving a going-concern audit opinion, and whether firm size moderates these relationships. The sample comprises 40 property and real-estate firms listed on the Indonesia Stock Exchange over 2018–2022 (N = 200 firm-year observations). Financial distress is proxied by Altman’s Z?-Score, abnormal cash flows are measured as discretionary deviations from expected operating cash flows, and firm size is captured by the natural logarithm of total assets. Logistic regressions are estimated in SPSS 26. Results show that higher financial distress significantly increases the probability of a going-concern opinion. In contrast, abnormal operating cash flows do not exhibit a statistically significant effect. Firm size moderates the distress–opinion link—larger firms facing distress are less likely to receive a going-concern qualification—indicating a pure moderation effect. Firm size does not, however, moderate the association between abnormal cash flows and the audit opinion. These findings highlight the primacy of traditional distress metrics in auditors’ going-concern judgments and suggest that organisational scale can temper the audit consequences of financial distress, whereas cash-flow abnormalities per se carry limited incremental weight in this setting. Keywords: Going Concern Audit Opinion; Financial distress; Abnormal cash flow from operating; Firm Size; Altman Z’Score.